Liberating Lithuania between the Helsinki and Belgrade Conferences: Crisis or New Impulses? - Banionis, Juozas (Genocidas ir rezistencija, 2011)
Following the easing of international tensions between East and West, the free Lithuanians in the West (or the political Lithuanian diaspora) were very concerned about the prospects for Lithuania’s liberation. The article reveals the ambiguous assessments of the impact of the Helsinki Conference (1975) on the struggle of Lithuanians in the West for Lithuania’s freedom and shows a search for a new quality for Lithuania’s liberation movement pending the Belgrade Conference (1977). The subject of the research is the most active Lithuanian organizations involved in the process and political activities, such as the Supreme Committee for the Liberation of Lithuania (SCLL, lith. VLIK), the Lithuanian American Council (LAC, lith. ALT), and the World Lithuanian Community (WLC, lith. PLB). The SCLL was the first Lithuanian political organization in the West, which drew attention to the process of the Conference on Security and Cooperation in Europe, and by way of memorandums expressed the expectations of the diaspora for the freedom of the Baltic States. After official assurance by the United States that the agreements in Helsinki would not change the stance of that country towards the Baltic States, the SCLL began constructive assessment of the principles of the Helsinki Final Act. They therefore set themselves the task, for the forthcoming conference in Belgrade, of implementing their political aspirations and testifying to the struggle of Lithuanians in the West for Lithuania’s freedom. The LAC, which supported the position of the liberation of Lithuania decisively, treated the Helsinki Final Act as providing new opportunities for their political activities. Convinced that the United States would continue its policy of non-recognition of the incorporation of the Baltic States into the USSR, LAC studied the essential legal and political aspects of the Helsinki Final Act and saw possible evolutionary internal developments of the Soviet Union. In preparation for the Belgrade Conference, LAC collected facts demonstrating violations of human rights and freedoms in Lithuania by the Soviets and this had the result of bringing Lithuanian expectations to international prominence. The WLC treated the Helsinki Final Act as the legitimisation of the USSR hegemony in Eastern Europe and therefore was sceptical about the liberation of Lithuania. However, in the long run – after a favourable resolution on the Baltic States by the US Congress and the new ideas proposed by the World Lithuanian Youth Association for liberation activities – the WLC drew attention to the violations of human rights in the Baltic States and found new arguments to support the struggle of Lithuanians in the West for Lithuania’s freedom. Lithuania’s Liberation Movement, which united the main political organizations of free Lithuanians in the West, arranged two conferences (in 1974 and 1975) during the period in question, devoted to liberation work. The liberation activity was mapped and prospective directions were outlined. Although there were various opinions, the necessity to coordinate the activities was agreed at the conferences. The liberation work was strengthened by bilateral meetings of the organizations (in 1976 and 1977). The idea of relating human rights violations in Soviet Lithuania with the issue of self-determination of the Lithuanian nation was proposed at the meetings. In the run-up to the signing of the Helsinki Final Act, the activities of the political entities of the Lithuanian, Latvian, and Estonian diaspora (World Baltic Conference and Joint Baltic American National Committee) intensified. They were concrete testimony to the rest of the world of the unchanging aspiration for freedom and independence of their nations as well as serving to remind the world about the occupation in the Baltic States.